IMPLEMENTATION OF THE NYIDAKIM SYSTEM IN IMMIGRATION SERVICES IN REPLACEMENT OF LOST / DAMAGED PASSPORTS AT KARAWANG IMMIGRATION OFFICE - Aditra Fajar Nurikhsan (Polteknik Imigrasi, 2019)
In carrying out its law enforcement functions, the Directorate General of Immigration has an Immigration Investigation and Enforcement Application (Nyidakim). Nyidakim is an application is used to assist the process of immigration law enforcement in the form of making an inspection report, creating an incident report and so on. One of the problems that exist in the nyidakim system is the problem in providing lost / damaged passport services with the nyidakim application, the Biometric Matching System (BMS) search system which sometimes has problems that takes 10 minutes or so to display, lack of integration with the passport service system on Travel Document section and others. This study uses a qualitative research methodology with descriptive qualitative methods through data collection techniques with observation and interviews. The results showed that the effectiveness of the information system had an effect on information management and the information system itself. If these two things do not go well, obstacles will arise that will hinder the effectiveness of an information system. conclusions that are considered to have succeeded in achieving the research objectives, namely this research has provided an explanation that the nyidakim application at the Class II Non TPI Karawang Immigration Office was carried out well and effectively in helping services for lost or damaged passports and the advice that can be given is that the immigration service process requires accuracy and speed so that the applicant can be satisfied with the performance of the UPT.